Inhibitory Effect of Punicalagin on Inflammatory and Angiogenic Activation of Human Umbilical Vein Endothelial Cells - Liu, Wei; Ou, Yanghui; Yang, Yumeng; Zhang, Xuemei; Huang, Liqi; Wang, Xiaohua; Wu, Buling; Huang, Mingcheng (Frontiers in Pharmacology, 2021)
Punicalagin, a major ellagitannin isolated from pomegranate, is known to have anti-cancer and anti-inflammatory activities, with an undefined therapeutic mechanism. The aim of this study was to investigate the effect of punicalagin on tumor necrosis factor alpha (TNF-α)-induced inflammation and angiogenic activation in human umbilical vein endothelial cells (HUVECs) and the potential mechanisms involved. Endothelia-leukocyte adhesion assays were used to assess primary cultures of HUVECs activation following TNF-α treatment. The endothelial cell proliferation, migration, and tube formation were evaluated using EdU assays, wound migration assays, and capillary-like tube formation assays, respectively. In addition, protein expression was measured using Western blot analysis. We found that punicalagin could reduce the adhesion of human monocyte cells to HUVECs in vitro and in vivo. Further, punicalagin decreased the expression of mRNA and the proteins VCAM-1 and ICAM1 in HUVECs. In addition, punicalagin inhibited permeability, proliferation, migration, and tube formation in VEGF-induced HUVECs, attenuated IKK-mediated activation of NF-κB pathway in TNF-α-induced endothelial cells, and suppressed VEGF-induced endothelial VEGFR2 activation and downstream P-pak1. Our findings indicate that punicalagin may exert a potent effect on HUVECs activation, and suggest that punicalagin functions via an endothelial based mechanism in the treatment of various diseases, including rheumatoid arthritis and cancer.